2022
DOI: 10.1371/journal.pone.0265422
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically disordered signaling proteins: Essential hub players in the control of stress responses in Saccharomyces cerevisiae

Abstract: Cells have developed diverse mechanisms to monitor changes in their surroundings. This allows them to establish effective responses to cope with adverse environments. Some of these mechanisms have been well characterized in the budding yeast Saccharomyces cerevisiae, an excellent experimental model to explore and elucidate some of the strategies selected in eukaryotic organisms to adjust their growth and development in stressful conditions. The relevance of structural disorder in proteins and the impact on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 99 publications
(116 reference statements)
0
3
0
Order By: Relevance
“…However, 24% of the hits were found to be intrinsically disordered using MobiDB ( https://mobidb.bio.unipd.it/ ; a protein is considered significantly disordered if the glutamine/asparagine content is more than 20% with a pWalz cutoff of 73,55) 37 . Previous studies have predicted 7.7% intrinsically disordered proteins in the yeast proteome 38 , indicating that intrinsically disordered proteins were enriched in our screen.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…However, 24% of the hits were found to be intrinsically disordered using MobiDB ( https://mobidb.bio.unipd.it/ ; a protein is considered significantly disordered if the glutamine/asparagine content is more than 20% with a pWalz cutoff of 73,55) 37 . Previous studies have predicted 7.7% intrinsically disordered proteins in the yeast proteome 38 , indicating that intrinsically disordered proteins were enriched in our screen.…”
Section: Resultsmentioning
confidence: 72%
“…24% of the proteins was found to contain intrinsically disordered regions. Previous studies have found that around 7.7% of the Saccharomyces cerevisiae proteome has some degree of disorder 38 . Thus there is a bias for intrinsically disordered proteins among foci-forming proteins in the get mutant analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Since protein repeats, characteristic of CWPs, have been associated with intrinsic disorder [61,62], a common way to form intermolecular complexes [63,64] and a necessary asset to secrete CWPs through the cell wall in bacteria [65], intrinsic disorder was assessed in identified PIRs (Table S2). In general, filamentous fungi PIRs (cluster 1B) were more intrinsically disordered (93.03% of total proteins had at least 1 intrinsically disordered region, IDR, longer than 50 amino acids; 99.31 % of total proteins had at least 1 IDR longer than 30 amino acids), than cluster 1A yeasts PIRs (77.6 % of total proteins had at least 1 IDR longer than 50 amino acids; 91.26 % of total proteins had at least 1 IDR longer than 30 amino acids).…”
Section: Pirs Are Intrinsically Disorderedmentioning
confidence: 99%